A porous high-efficiency carbon enhancer using waste graphite electrodes and a preparation method thereof
By using a carbon enhancer made of various raw materials such as waste graphite electrodes, combined with impurity removal and addition of silica, the problems of many impurities and poor carbon enhancement effects in existing carbon enhancers are solved, and a high carbon content and multi-purpose carbon enhancement effect is achieved.
Patent Information
- Application Number
- CN202411975834.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
Existing carbon enhancers contain a large amount of impurities, which affects the smelting process and product quality, and have poor carbon enhancement effects and a single application scenario.
Carbon enhancers are made using waste graphite electrodes, petroleum coke, asphalt coke, anthracite and wood carbon, and the carbon content is increased through impurity removal treatment, and silica is added to evenly distribute carbon elements.
It improves the carbon content and purity of the carbon enhancer, reduces the impurity content, enhances the physical and chemical properties of steel, and is suitable for different industrial application scenarios.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of recarburizers, in particular to a porous high-efficiency recarburizer utilizing waste graphite electrodes and a preparation method thereof. Background Art
[0002] In the smelting process of steel products, the smelting loss of carbon elements in the molten iron is often increased due to factors such as long smelting time, insulation time, and overheating time, resulting in a decrease in the carbon content in the molten iron, which leads to the carbon content in the molten iron failing to reach the expected theoretical value of refining. The carbon-containing substances added to make up for the carbon content burned during the steel smelting process are called recarburizers. There are many kinds of raw materials for recarburizers, and the production processes are also different. There are wood carbon, coal carbon, coke, graphite, etc., and there are many small categories under each category. High-quality recarburizers generally refer to recarburizers that have been graphitized. Under high temperature conditions, the arrangement of carbon atoms is in the microscopic form of graphite, so it is called graphitization. Graphitization can reduce the content of impurities in the recarburizer, increase the carbon content of the recarburizer, and reduce the sulfur content. When used in casting, recarburizers can greatly increase the amount of scrap steel, reduce the amount of pig iron, or even eliminate pig iron. Existing recarburizers contain a large amount of impurities, and the impurities in the recarburizers mainly include ash, volatile matter, sulfur, etc. These impurities will have many effects on the smelting process and product quality: high ash content will lead to a large amount of smoke and slag in the smelting process, increase energy consumption and slag removal labor intensity, and may pollute the molten iron; too high sulfur content will affect the spheroidization effect, especially in the production of ductile iron and vermicular cast iron; therefore, the selection and treatment of recarburizer raw materials are particularly important, and the existing recarburizers have poor recarburization effect, often use a single raw material, and the application scenario is relatively single. Therefore, a porous and efficient recarburizer using waste graphite electrodes and a preparation method thereof are provided. Summary of the invention
[0003] The purpose of the present invention is to provide a porous high-efficiency recarburizer using waste graphite electrodes and a preparation method thereof in view of the defects of the prior art, so as to solve the problems raised by the above-mentioned background technology.
[0004] To achieve the above object, the present invention provides the following technical solution: a porous high-efficiency recarburizer using waste graphite electrodes, which is made of the following raw materials in parts by weight: 50-55 parts of waste graphite electrodes, 10-15 parts of petroleum coke, 10-15 parts of asphalt coke, 10-15 parts of anthracite, 10-15 parts of wood carbon, 1-2 parts of silicon dioxide, 5-8 parts of foaming agent, and 100-300 parts of water;
[0005] The foaming agents are carbon black and sodium bicarbonate, and the mass ratio of carbon black to sodium bicarbonate is 7:3.
[0006] A method for preparing a porous high-efficiency recarburizer using waste graphite electrodes, the specific steps are as follows:
[0007] Step 1: impurity removal of waste graphite electrodes;
[0008] Step 1.1: Grind the waste graphite electrode into graphite powder;
[0009] Step 1.2: Rinse the graphite powder with sulfuric acid to generate gray-white solid copper sulfate particles, and then filter the copper sulfate particles;
[0010] Step 1.3: The graphite powder filtered by acid washing is then placed in a KOH solution to generate potassium silicate precipitation, and then the potassium silicate precipitation is filtered to obtain pure waste graphite electrode powder;
[0011] Step 2: impurity removal of petroleum coke and anthracite;
[0012] Step 2.1: drying the petroleum coke and anthracite, and then grinding them into petroleum coke and anthracite powder;
[0013] Step 2.2: washing the petroleum coke and anthracite powder to remove ash, sulfur and other soluble impurities in the petroleum coke and anthracite powder to obtain a pure petroleum coke and anthracite mixed powder;
[0014] Step 2.3: Drying the pure petroleum coke and anthracite powder;
[0015] Step 3: impurity removal of asphalt coke;
[0016] Step 3.1: Grind the dried pitch coke into pitch coke powder.
[0017] Step 3.2: adding sodium hydroxide to the asphalt coke powder to convert the sulfur into sodium sulfide, and filtering the sodium sulfide to obtain pure asphalt coke powder;
[0018] Step 4: Grind the wood carbon into wood carbon powder, grind the silicon dioxide into silicon dioxide powder, put the pure waste graphite electrode powder, the pure petroleum coke and anthracite mixed powder, the asphalt coke powder, the silicon dioxide powder and the wood carbon powder into an appropriate amount of water, and then stir at a high speed for 15-30 minutes, and then add a foaming agent and heat to 350 to 400 degrees Celsius, stir for 5-10 minutes, and obtain a mixture;
[0019] Step 5: Use a ball press to press the mixture into a green body with a particle size of 2-3 cm and a length of 3-5 cm. Then dry the green body at 150-300 degrees Celsius for 1-2 hours. When the green body is cooled to room temperature, the finished product is obtained.
[0020] As a preferred technical solution of the present invention, the particle size of the graphite powder in step 1.1 is 0.3-0.6 mm.
[0021] As a preferred technical solution of the present invention, the particle size of the petroleum coke and anthracite powder in step 2.1 is 0.7-1 mm.
[0022] As a preferred technical solution of the present invention, the particle size of the wood carbon powder in step 4 is 0.5-1 mm.
[0023] As a preferred technical solution of the present invention, the sulfuric acid in step 1.2 and the KOH in step 1.3 are both in excess.
[0024] As a preferred technical solution of the present invention, the particle size of the silicon dioxide powder is 90-100 μm.
[0025] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention adopts waste graphite electrodes, petroleum coke, asphalt coke, anthracite and wood carbon to make a recarburizer, and the waste graphite electrodes, petroleum coke, asphalt coke and anthracite are all treated by impurity removal to increase the carbon content of the recarburizer. The present invention uses waste graphite electrodes as the main raw material for preparing the recarburizer, thereby achieving the purpose of waste recycling and avoiding environmental pollution; and the foaming agent adopts carbon black and sodium bicarbonate, even if the carbon black is not completely used up, it can be used to increase the carbon content of the recarburizer, which not only avoids waste of resources, but also avoids adding new impurities, and silicon dioxide is added to the recarburizer of the present invention, and the silicon dioxide powder has high fineness. After addition, the carbon in the steel can be evenly distributed, the chemical composition of the steel is stabilized, and the physical and chemical properties of the steel are improved, which is suitable for different industrial application scenarios. DETAILED DESCRIPTION
[0026] The preferred embodiments of the present invention are described in detail below so that the advantages and features of the present invention can be more easily understood by those skilled in the art, thereby making a clearer and more definite definition of the protection scope of the present invention.
[0027] Example 1: A method for preparing a porous high-efficiency recarburizer using waste graphite electrodes, which is prepared from the following raw materials in parts by weight: 50 parts of waste graphite electrodes, 10 parts of petroleum coke, 10 parts of asphalt coke, 10 parts of anthracite, 10 parts of wood carbon, 1 part of silicon dioxide, 5 parts of foaming agent, and 100 parts of water;
[0028] The foaming agents are carbon black and sodium bicarbonate, and the mass ratio of carbon black to sodium bicarbonate is 7:3.
[0029] The specific preparation method is as follows:
[0030] Step 1: impurity removal of waste graphite electrodes;
[0031] Step 1.1: Grind the waste graphite electrode into graphite powder, the particle size of the graphite powder is 0.3-0.6mm;
[0032] Step 1.2: Rinse the graphite powder with sulfuric acid to generate gray-white solid copper sulfate particles, and then filter the copper sulfate particles;
[0033] Step 1.3: The graphite powder filtered by acid washing is then placed in a KOH solution to generate potassium silicate precipitation, and then the potassium silicate precipitation is filtered to obtain pure waste graphite electrode powder;
[0034] Step 2: impurity removal of petroleum coke and anthracite;
[0035] Step 2.1: drying the petroleum coke and anthracite, and then grinding them into petroleum coke and anthracite powders, wherein the particle size of the petroleum coke and anthracite powders is 0.7-1 mm;
[0036] Step 2.2: washing the petroleum coke and anthracite powder to remove ash, sulfur and other soluble impurities in the petroleum coke and anthracite powder to obtain a pure petroleum coke and anthracite mixed powder;
[0037] Step 2.3: Drying the pure petroleum coke and anthracite powder;
[0038] Step 3: impurity removal of asphalt coke;
[0039] Step 3.1: Grind the dried pitch coke into pitch coke powder.
[0040] Step 3.2: adding sodium hydroxide to the asphalt coke powder to convert the sulfur into sodium sulfide, and filtering the sodium sulfide to obtain pure asphalt coke powder;
[0041] Step 4: Grind the wood carbon into wood carbon powder, the particle size of the wood carbon powder is 0.5-1mm, grind the silicon dioxide into silicon dioxide powder, the particle size of the silicon dioxide powder is 90-100μm, put the pure waste graphite electrode powder, the pure petroleum coke and anthracite mixed powder, the asphalt coke powder, the silicon dioxide powder and the wood carbon powder into an appropriate amount of water, and then stir at a high speed for 15-30min, then add a foaming agent and heat to 350 to 400 degrees Celsius, stir for 5-10min, and obtain a mixture;
[0042] Step 5: Use a ball press to press the mixture into a green body with a particle size of 2-3 cm and a length of 3-5 cm. Then dry the green body at 150-300 degrees Celsius for 1-2 hours. When the green body is cooled to room temperature, the finished product is obtained.
[0043] Example 2: A method for preparing a porous high-efficiency recarburizer using waste graphite electrodes, which is prepared from the following raw materials in parts by weight: 53 parts of waste graphite electrodes, 12 parts of petroleum coke, 12 parts of asphalt coke, 12 parts of anthracite, 12 parts of wood carbon, 1.3 parts of silicon dioxide, 6 parts of foaming agent, and 150 parts of water;
[0044] The foaming agents are carbon black and sodium bicarbonate, and the mass ratio of carbon black to sodium bicarbonate is 7:3.
[0045] The specific preparation method is as follows:
[0046] Step 1: impurity removal of waste graphite electrodes;
[0047] Step 1.1: Grind the waste graphite electrode into graphite powder, the particle size of the graphite powder is 0.3-0.6mm;
[0048] Step 1.2: Rinse the graphite powder with sulfuric acid to generate gray-white solid copper sulfate particles, and then filter the copper sulfate particles;
[0049] Step 1.3: The graphite powder filtered by acid washing is then placed in a KOH solution to generate potassium silicate precipitation, and then the potassium silicate precipitation is filtered to obtain pure waste graphite electrode powder;
[0050] Step 2: impurity removal of petroleum coke and anthracite;
[0051] Step 2.1: drying the petroleum coke and anthracite, and then grinding them into petroleum coke and anthracite powders, wherein the particle size of the petroleum coke and anthracite powders is 0.7-1 mm;
[0052] Step 2.2: washing the petroleum coke and anthracite powder to remove ash, sulfur and other soluble impurities in the petroleum coke and anthracite powder to obtain a pure petroleum coke and anthracite mixed powder;
[0053] Step 2.3: Drying the pure petroleum coke and anthracite powder;
[0054] Step 3: impurity removal of asphalt coke;
[0055] Step 3.1: Grind the dried pitch coke into pitch coke powder.
[0056] Step 3.2: adding sodium hydroxide to the asphalt coke powder to convert the sulfur into sodium sulfide, and filtering the sodium sulfide to obtain pure asphalt coke powder;
[0057] Step 4: Grind the wood carbon into wood carbon powder, the particle size of the wood carbon powder is 0.5-1mm, grind the silicon dioxide into silicon dioxide powder, the particle size of the silicon dioxide powder is 90-100μm, put the pure waste graphite electrode powder, the pure petroleum coke and anthracite mixed powder, the asphalt coke powder, the silicon dioxide powder and the wood carbon powder into an appropriate amount of water, and then stir at a high speed for 15-30min, then add a foaming agent and heat to 350 to 400 degrees Celsius, stir for 5-10min, and obtain a mixture;
[0058] Step 5: Use a ball press to press the mixture into a green body with a particle size of 2-3 cm and a length of 3-5 cm. Then dry the green body at 150-300 degrees Celsius for 1-2 hours. When the green body is cooled to room temperature, the finished product is obtained.
[0059] Example 3: A method for preparing a porous high-efficiency recarburizer using waste graphite electrodes, which is prepared from the following raw materials in parts by weight: 55 parts of waste graphite electrodes, 15 parts of petroleum coke, 15 parts of asphalt coke, 15 parts of anthracite, 15 parts of wood carbon, 2 parts of silicon dioxide, 8 parts of foaming agent, and 200 parts of water;
[0060] The foaming agents are carbon black and sodium bicarbonate, and the mass ratio of carbon black to sodium bicarbonate is 7:3.
[0061] The specific preparation method is as follows:
[0062] Step 1: impurity removal of waste graphite electrodes;
[0063] Step 1.1: Grind the waste graphite electrode into graphite powder, the particle size of the graphite powder is 0.3-0.6mm;
[0064] Step 1.2: Rinse the graphite powder with sulfuric acid to generate gray-white solid copper sulfate particles, and then filter the copper sulfate particles;
[0065] Step 1.3: The graphite powder filtered by acid washing is then placed in a KOH solution to generate potassium silicate precipitation, and then the potassium silicate precipitation is filtered to obtain pure waste graphite electrode powder;
[0066] Step 2: impurity removal of petroleum coke and anthracite;
[0067] Step 2.1: drying the petroleum coke and anthracite, and then grinding them into petroleum coke and anthracite powders, wherein the particle size of the petroleum coke and anthracite powders is 0.7-1 mm;
[0068] Step 2.2: washing the petroleum coke and anthracite powder to remove ash, sulfur and other soluble impurities in the petroleum coke and anthracite powder to obtain a pure petroleum coke and anthracite mixed powder;
[0069] Step 2.3: Drying the pure petroleum coke and anthracite powder;
[0070] Step 3: impurity removal of asphalt coke;
[0071] Step 3.1: Grind the dried pitch coke into pitch coke powder.
[0072] Step 3.2: adding sodium hydroxide to the asphalt coke powder to convert the sulfur into sodium sulfide, and filtering the sodium sulfide to obtain pure asphalt coke powder;
[0073] Step 4: Grind the wood carbon into wood carbon powder, the particle size of the wood carbon powder is 0.5-1mm, grind the silicon dioxide into silicon dioxide powder, the particle size of the silicon dioxide powder is 90-100μm, put the pure waste graphite electrode powder, the pure petroleum coke and anthracite mixed powder, the asphalt coke powder, the silicon dioxide powder and the wood carbon powder into an appropriate amount of water, and then stir at a high speed for 15-30min, then add a foaming agent and heat to 350 to 400 degrees Celsius, stir for 5-10min, and obtain a mixture;
[0074] Step 5: Use a ball press to press the mixture into a green body with a particle size of 2-3 cm and a length of 3-5 cm. Then dry the green body at 150-300 degrees Celsius for 1-2 hours. When the green body is cooled to room temperature, the finished product is obtained.
[0075] The carbon content of the products obtained in Examples 1-3 was tested by thermogravimetric analysis; and a carburizer was purchased on the market as a comparative example. The specific test data are shown in Table 1:
[0076] Table 1: Carbon content and impurities of the products of Examples 1-3 and Comparative Examples
[0077] Carbon content (%) Impurities(%) Example 1 98.5-99.4 0.6-1.5 Example 2 99.1-99.7 0.3-0.9 Example 3 98.9-99.3 0.7-1.1 Comparative Example 93.1-95.5 4.5-6.9
[0078] In summary, the recarburizer prepared by the method of the present invention has a high carbon content and few impurities. Moreover, the recarburizer of the present invention contains a variety of raw materials such as waste graphite electrodes, petroleum coke, asphalt coke, anthracite and wood carbon, and is suitable for different industrial application scenarios.
[0079] The above embodiments only express the implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention.
Claims
1. A porous high-efficiency recarburizer using waste graphite electrodes, characterized in that: Made from the following raw materials in parts by weight: 50-55 parts of waste graphite electrode, 10-15 parts of petroleum coke, 10-15 parts of asphalt coke, 10-15 parts of anthracite, 10-15 parts of wood carbon, 1-2 parts of silicon dioxide, 5-8 parts of foaming agent, and 100-300 parts of water; The foaming agents are carbon black and sodium bicarbonate, and the mass ratio of carbon black to sodium bicarbonate is 7:
3.
2. A method for preparing a porous high-efficiency recarburizer using waste graphite electrodes as claimed in claim 1, characterized in that: The specific steps are as follows: Step 1: impurity removal of waste graphite electrodes; Step 1.1: Grind the waste graphite electrode into graphite powder; Step 1.2: Rinse the graphite powder with sulfuric acid to generate gray-white solid copper sulfate particles, and then filter the copper sulfate particles; Step 1.3: The graphite powder filtered by acid washing is then placed in a KOH solution to generate potassium silicate precipitation, and then the potassium silicate precipitation is filtered to obtain pure waste graphite electrode powder; Step 2: impurity removal of petroleum coke and anthracite; Step 2.1: drying the petroleum coke and anthracite, and then grinding them into petroleum coke and anthracite powder; Step 2.2: washing the petroleum coke and anthracite powder to remove ash, sulfur and other soluble impurities in the petroleum coke and anthracite powder to obtain a pure petroleum coke and anthracite mixed powder; Step 2.3: Drying the pure petroleum coke and anthracite powder; Step 3: impurity removal of asphalt coke; Step 3.1: Grind the dried pitch coke into pitch coke powder. Step 3.2: adding sodium hydroxide to the asphalt coke powder to convert the sulfur into sodium sulfide, and filtering the sodium sulfide to obtain pure asphalt coke powder; Step 4: Grind the wood carbon into wood carbon powder, grind the silicon dioxide into silicon dioxide powder, put the pure waste graphite electrode powder, the pure petroleum coke and anthracite mixed powder, the asphalt coke powder, the silicon dioxide powder and the wood carbon powder into an appropriate amount of water, and then stir at a high speed for 15-30 minutes, and then add a foaming agent and heat to 350 to 400 degrees Celsius, stir for 5-10 minutes, and obtain a mixture; Step 5: Use a ball press to press the mixture into a green body with a particle size of 2-3 cm and a length of 3-5 cm. Then dry the green body at 150-300 degrees Celsius for 1-2 hours. When the green body is cooled to room temperature, the finished product is obtained.
3. The method for preparing a porous high-efficiency recarburizer using waste graphite electrodes according to claim 2, characterized in that: The particle size of the graphite powder in step 1.1 is 0.3-0.6 mm.
4. The method for preparing a porous high-efficiency recarburizer using waste graphite electrodes according to claim 2, characterized in that: The particle size of the petroleum coke and anthracite powder in step 2.1 is 0.7-1 mm.
5. The method for preparing a porous high-efficiency recarburizer using waste graphite electrodes according to claim 2, characterized in that: The particle size of the wood carbon powder in step 4 is 0.5-1 mm.
6. The method for preparing a porous high-efficiency recarburizer using waste graphite electrodes according to claim 2, characterized in that: The sulfuric acid in step 1.2 and the KOH in step 1.3 are both in excess.
7. The method for preparing a porous high-efficiency recarburizer using waste graphite electrodes according to claim 2, characterized in that: The particle size of the silicon dioxide powder is 90-100 μm.
Citation Information
Cited By
Method for preparing graphene and graphene
CN121063525A